2017
DOI: 10.1007/s00268-017-4019-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of MEN1 GEP‐NET: Single‐Center Experience After a Long Follow‐Up

Abstract: Background The multiple endocrine neoplasia type 1 syndrome (MEN1) natural history is poorly evaluated, and few single-institution experiences about hereditary gastroenteropancreatic neuroendocrine tumors (GEP-NET) are reported. Our purpose is to analyze the role of GEP-NET in MEN1-related death, as well as the behavior of these lesions during follow-up. Methods The study population consists of 77 patients diagnosed with MEN1 GEP-NET, regularly followed up since 1990. Extensive clinical data were prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
0
21
1
Order By: Relevance
“…Yamazaki et al reported delays of MEN1 diagnosis from -2.9 to 5.3 years, depending on different signs, tumours and proband/family member status [24]. Giudici et al observed 5.7 years of delay from GEP-NET to MEN1 diagnosis, which is significantly longer than observed in our database [27]. Leeuvaarde et al described markedly longer delays in diagnosis of particular lesions, but the authors analysed only non-index cases, and the delays decreased in the course of time [23].…”
Section: Discussioncontrasting
confidence: 56%
“…Yamazaki et al reported delays of MEN1 diagnosis from -2.9 to 5.3 years, depending on different signs, tumours and proband/family member status [24]. Giudici et al observed 5.7 years of delay from GEP-NET to MEN1 diagnosis, which is significantly longer than observed in our database [27]. Leeuvaarde et al described markedly longer delays in diagnosis of particular lesions, but the authors analysed only non-index cases, and the delays decreased in the course of time [23].…”
Section: Discussioncontrasting
confidence: 56%
“…Bone metastasis are reported in 4-12% of NET patients, but the real incidence is probably higher [13][14][15][16]. However, except for those patients who have a metastatic disease associated with shorter survival [13], patients with NET usually have good long-term survival [10,17]. It has been demonstrated that NET patients have a greater clinical burden of disease than matched control subjects, with increased risk of cardiovascular, hepatic, and gastrointestinal diseases, as well as osteopenia and osteoporosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Of the three major manifestations, PHPT has the highest penetrance and is considered to appear first in MEN1, although it often remains unrecognised [5]. Recent publications show, that functionally active GEP-NETs, initially frequently diagnosed as sporadic ones, lead to diagnosis of MEN1 in a remarkable proportion of patients [6]. Compared to sporadic tumors, MEN1-associated GEP-NETs are diagnosed 10 years earlier and often in a multiple form [5, 7], and their penetrance is as high as 80–90%, reaching nearly that of the parathyroid adenomas [6].…”
Section: Introductionmentioning
confidence: 99%